2022
DOI: 10.3390/coasts2030009
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Cultural Understanding as a Basis for Management of a Globally Significant Island Landscape

Abstract: Islands provide the opportunity to explore management regimes and research issues related to the isolation, uniqueness, and integrity of ecological systems. K’gari (Fraser Island) is an Australian World Heritage property listed based on its outstanding natural value, specifically, the unique wilderness characteristics and the diversity of ecosystem types. Our goal was to draw on an understanding of the natural and cultural environment of K’gari as a foundation on which to build a management model that includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 143 publications
0
2
0
Order By: Relevance
“…Further details on the nature of the study site can be found in Wardell-Johnson et al (2015) and Walker et al (2022).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Further details on the nature of the study site can be found in Wardell-Johnson et al (2015) and Walker et al (2022).…”
Section: Study Sitementioning
confidence: 99%
“…Many indigenous people across Australia have a long and shared history and strong affinity for dingoes (Hytten, 2009; Koungoulos, 2021; Rose, 2000; Smith & Litchfield, 2009), including Butchulla people (Carter et al., 2017; Phoenix‐O'Brien, 2002). Contemporary society also highly values dingoes (Van Eeden et al., 2020), and those on K'gari are a major drawcard for over 400,000 tourists visiting the island each year (Thompson et al., 2003; Walker et al., 2022). Dingoes on the island are also a genetically distinct population (Conroy et al., 2017, 2021), and a substantial amount of resources and funding are devoted to conserving and protecting K'gari dingoes (Behrendorff, 2021; Tapply, 2018).…”
Section: Introductionmentioning
confidence: 99%